Macroeconomics Demystified - Swanenberg August (McGraw -Hill, 2005)
"Macroeconomics Demystified" offers students of all levels unique and easy-to-understand explanations of macroeconomic principles. "Macroeconomics Demystified" teaches the material in a college-level course in a friendly, informal manner. While covering the whole breadth of the topic, it is not meant to be a textbook, but rather serve as a self-teach companion guide to textbooks. It does not assume any previous knowledge of macroeconomics, microeconomics, or mathematics. "Macroeconomics Demystified" offers a clear presentation of concepts, applications, and examples, with the right mix of text and graphics.